Pengaruh Senam Aerobik Terhadap Premenstrual Syndrome pada Siswi Sekolah Menengah Atas (SMA) - Kusuma, Anggi (Wellness And Healthy Magazine, 2019)
Women often complain comes a variety of disorders either before or while menstruating. Disruption before menstruation is known as premenstrual syndrome (PMS). About 14 percent of premenstrual syndrome could strongly effect that requires them to take a break from school or office. This study aims to know the effect of aerobic exercise on premenstrual syndrome in girls at SMA N 1 Indralaya. This study is a pre-experimental research with quantitative approach. Sample in this research was 33 female students who have premenstrual syndrome. Thirty-three students were gotten aerobic exercise 2 times a week for 4 weeks with low intensity and in 45 minutes. The premenstrual syndrome symptoms were measured by using premenstrual syndrome symptoms questionnaire which modified from the Menstrual Distress Questionnaire (MDQ) and Rayburn premenstrual syndrome symptoms table. The data were analyzed by using Wilcoxon Signed Ranks Test. with significance level at 0.05. The results of this study obtained the average score of symptoms of premenstrual syndrome before aerobics is 45.93 while the average score of symptoms of premenstrual syndrome post-aerobics is 40.72. Symptoms of premenstrual syndrome in student with premenstrual syndrome after getting aerobic exercise significantly reduced (p = 0.001) which means that aerobic exercise effected on premenstrual syndrome.